Temperature effect on triacylglycerol species in seed oil from high stearic sunflower lines with different genetic backgrounds. - Izquierdo, Natalia Gabriela; Martínez-Force, Enrique; Garces, Rafael; Aguirrezabal, Luis Adolfo Nazareno; Zambelli, Andrés; Reid, Roberto (John Wiley & Sons, 2019)
BACKGROUND: This study characterized the influence of temperature during grain filling on the saturated fatty acid distribution in triacylglycerol molecules from high stearic sunflower lines with different genetic backgrounds. Two growth chamber experiments were conducted with day/night temperatures of 16/16, 26/16, 26/26 and 32/26 °C. RESULTS: In all genotypes, independently of the genetic background, higher temperatures increased palmitic and oleic acid and reduced linoleic acid concentrations. Increasing night temperature produced an increase in saturated-unsaturated-saturated species, indicating a more symmetrical distribution of saturated fatty acids. The solid fat index was more affected by temperature during grain filling in lines with high linoleic than high oleic background. Higher variations in symmetry among night temperatures were observed in lines with high oleic background, which are more stable in fatty acid composition. CONCLUSION: The effect of temperature on triacylglycerol composition is not completely explained by its effect on fatty acid composition. Thus night temperature affects oil properties via its effects on fatty acid synthesis and on the distribution of fatty acids in the triacylglycerol molecules.